PENGARUH LAYANAN INFORMASI CARA BELAJAR EFEKTIF TERHADAP KEMANDIRIAN BELAJAR SISWA PADA KELAS XI DI SMA - Rizul, Hantika Januyah; M. Asrori, M. Asrori; Purwanti, Purwanti (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe problem in this research is that some students learn only by depending on their friends, not discipline while studying, often cheat, do not pay attention when the teacher explain the lesson so that learners can not understand the lesson that has been given by subject teacher. The purpose of this research is to know if there is influence of information service effective way to student independence in class XI in SMA academic year. The method used is descriptive method with relationship study form and using quantitative approach. The data collection tools used are observation, questionnaire and interview. Based on the results of data analysis shows that the effect of information services on how effective learning on student self-reliance in high school reaches a score of 96% in the high category while the independence of learning in high school students reached an 83% score in the high category. The result of determination index calculation to find out the influence of information service on effective learning method toward student's learning independence in SMA using formula x 2 = 100% = 2500% = 2500% = meaning of information service contribution effective learning towards learning independence is 25% and there are still 75% other variables not examined in this study. Learners are influenced by other variables not obtained in this study. Based on the explanation can be concluded that, there is a significant influence that is 25% of the influence of information services effective way of learning to the independence of students in high school.Keywords :Information Services, How effevtive learning, Learning IndependenceÂ